Community Standing in Social Services: Focus on its Importance in Vulnerable Neighborhoods - Jaraíz Arroyo, Germán (Cuadernos de Trabajo Social, 2012)
This article analyzes the importance that the community-based approach has taken in modern Social Services. In the first part, the evolution that the subject has experienced since configuration of these mechanisms up to the current time is described. The second part focuses on the practical implementation of community work, using the perceptions and speeches of Social Service professionals in vulnerable neighborhoods in a large city of the Andalusian region as supporting evidence. The final part plumbs the mentality which characterizes community intervention while identifying the limits and contributions of professionals seeking its improvement.